ADRIAN BROWN, Practical Digital Preservation: A How-To Guide for Organizations of Any Size - Mircea, Gabriela (Archivaria, 2014)
Practical Digital Preservation: A How-To Guide for Organizations of Any Size. ADRIAN BROWN. Chicago: Neal-Schuman, an imprint of the American Library Association, 2013. xvi, 336 pp. ISBN 978-1-55570-942-6.